2017
DOI: 10.1097/hrp.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Connectivity in the Human Connectome Project: Current Status and Relevance to Understanding Psychopathology

Abstract: A key tenet of modern psychiatry is that psychiatric disorders arise from abnormalities in brain circuits that support human behavior. Our ability to examine hypotheses around circuit level abnormalities in psychiatric disorders has been made possible by advances in human neuroimaging technologies. These advances have provided the basis for recent efforts in the field to develop a more complex understanding of the function of brain circuits in health and of their relationship to behavior, which in turns provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…Indeed, by using methods that quantify global patterns of activation or ‘brain states’, researchers have successfully predicted the fate of a memory from fMRI data (Balci, et al, 2008; Rissman, Greely, & Wagner, 2010; Rissman & Wagner, 2012). In another instance, using data from the Human Connectome Project (HCP) and the United Kingdom Biobank Project, researchers can combine genetic and brain connectome metrics to investigate the dual influences of genetic and environmental factors in the development of cognitive abilities (Barch, 2017; Rosenberg, et al, 2016; Shen, et al, 2017). Although studies utilizing connectome data to investigate the development of memory are scarce, progress in the application of novel multivariate methods to understand memory in adults presents a promising direction for investigating the sources of its development in younger samples.…”
Section: Future Directions Made Possible By the Utilization Of Big Datamentioning
confidence: 99%
“…Indeed, by using methods that quantify global patterns of activation or ‘brain states’, researchers have successfully predicted the fate of a memory from fMRI data (Balci, et al, 2008; Rissman, Greely, & Wagner, 2010; Rissman & Wagner, 2012). In another instance, using data from the Human Connectome Project (HCP) and the United Kingdom Biobank Project, researchers can combine genetic and brain connectome metrics to investigate the dual influences of genetic and environmental factors in the development of cognitive abilities (Barch, 2017; Rosenberg, et al, 2016; Shen, et al, 2017). Although studies utilizing connectome data to investigate the development of memory are scarce, progress in the application of novel multivariate methods to understand memory in adults presents a promising direction for investigating the sources of its development in younger samples.…”
Section: Future Directions Made Possible By the Utilization Of Big Datamentioning
confidence: 99%
“…99,100 Functional connectivity fingerprints appear to stabilize during adolescent development, 101 and there is evidence that both delayed stabilization and particular patterns of whole-brain connectivity are associated with certain cognitive-affective traits 102 and psychiatric disorders. 103 For example, in a large sample of over 1,100 patients with depression, Drysdale and colleagues recently showed that distinct patterns of functional connectivity across limbic and frontostriatal networks could be used to group patients with depression into four subtypes with different clinical-symptom profiles 104 – putative endophenotypes. One of the most studied non-invasive methods for modulating neural circuits is transcranial magnetic stimulation (TMS) (reviewed in 105 ) which applies a rapidly changing magnetic field to the scalp to induce currents that can either excite or inhibit the underlying cortex depending on the frequency of stimulation.…”
Section: Precision Psychiatry and Neurosciencementioning
confidence: 99%
“…In line with this, studies including patients with psychological disorders with reduced ability to regulate emotions (e.g., depression and anxiety) have found deficits in functional and effective connectivity between the amygdala and frontal brain regions (Erk et al, 2010 ; Cullen et al, 2011 ; Niedtfeld et al, 2012 ; Clauss et al, 2014 ; Mochcovitch et al, 2014 ; Radaelli et al, 2015 ; Picó-Pérez et al, 2017 ). Additionally, there is evidence that not only task-related connectivity but also alterations in resting-state functional connectivity of (among others) PFC, amygdala, and insula are associated with depression and anxiety (Menon, 2011 ; Zhang et al, 2014 ; Barch, 2017 ). Resting-state functional brain connectivity (rsFC) reflects intrinsic connectivity, which is correlated temporal patterns among brain regions during rest.…”
Section: Introductionmentioning
confidence: 99%